2016
DOI: 10.1016/j.ejmech.2016.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of new aryl-alkyl(alkenyl)-4-benzylpiperidines, novel Sigma Receptor (SR) modulators, as potential anticancer-agents

Abstract: In the early 2000s, the Sigma Receptor (SR) family was identified as potential "druggable" target in cancer treatment. Indeed, high density of SRs was found in breast, lung, and prostate cancer cells, supporting the idea that SRs could play a role in tumor growth and progression. Moreover, a link between the degree of SR expression and tumor aggressiveness has been postulated, justified by the presence of SRs in high metastatic-potential cancer cells. As a consequence, considerable efforts have been devoted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…Over the years, pharmacological, chemical, and biological papers have demonstrated that S2R is a potential therapeutic target for several diseases including neurodegenerative disorders and cancer ( Vilner and Bowen, 1993 ; Vilner et al, 1995 ; Bowen, 2000 ; Wheeler et al, 2000 ; Crawford and Bowen, 2002 ; Kashiwagi et al, 2009 ; Hornick et al, 2010 ; Guo and Zhen, 2015 ). Based on indirect evidence of S2R overexpression in peripheral and cerebral tumors, it has been hypothesized as a potential target for anticancer therapy ( Crawford and Bowen, 2002 ; Crawford et al, 2002 ; Rui et al, 2016 ), and S2R radiotracers have been developed to image tumors ( Tu et al, 2005 , 2007 , 2010 ; Mach and Wheeler, 2009 ; Mach et al, 2009 ). However, despite the numerous studies performed to date in this setting, the unknown molecular identity of the receptor has limited biological investigations and hindered the search for new drugs that act via the S2R pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, pharmacological, chemical, and biological papers have demonstrated that S2R is a potential therapeutic target for several diseases including neurodegenerative disorders and cancer ( Vilner and Bowen, 1993 ; Vilner et al, 1995 ; Bowen, 2000 ; Wheeler et al, 2000 ; Crawford and Bowen, 2002 ; Kashiwagi et al, 2009 ; Hornick et al, 2010 ; Guo and Zhen, 2015 ). Based on indirect evidence of S2R overexpression in peripheral and cerebral tumors, it has been hypothesized as a potential target for anticancer therapy ( Crawford and Bowen, 2002 ; Crawford et al, 2002 ; Rui et al, 2016 ), and S2R radiotracers have been developed to image tumors ( Tu et al, 2005 , 2007 , 2010 ; Mach and Wheeler, 2009 ; Mach et al, 2009 ). However, despite the numerous studies performed to date in this setting, the unknown molecular identity of the receptor has limited biological investigations and hindered the search for new drugs that act via the S2R pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports describe the antiproliferative and anticancer activity of σ2R ligands in variable cell lines and tumors [ 32 , 120 , 121 ] ( Table 1 ). The last years, it has become obvious that σ2R ligands have significant role in anticancer therapy, as they provoke cancer cell death [ 32 , 121 ]. Siramesine was active against all cancer cell lines tested.…”
Section: σ-Receptor (σR) Ligands In Cancer Researchmentioning
confidence: 99%
“…Both σR types are overexpressed in numerous human cancer tissues, such as small- and non-small-cell lung carcinoma [ 24 , 32 ], large-cell carcinoma (NCI-H1299 and NCI-H838) [ 33 ], renal carcinoma [ 24 ], colon carcinoma (HCT-15 and HCT-16) [ 34 ], sarcoma [ 33 ], brain tumors (CNS U51) [ 35 ], breast cancer (MCF-7. T47D and SKBr3) and breast ductal carcinoma (T47D) [ 32 ], melanoma (A375) [ 24 ], glioblastoma [ 24 ], adenocarcinoma (line 66), neuroblastoma (BE(2) and SK-N-SH) [ 24 ], prostate cancer (DU-145, PC3 and LnCap) [ 24 ], pancreas (MiaPaca2 and BX-PC3), liver (SKHep1), ovarian carcinoma (ICROV-1 and OVCAR-5) and leukemia (HL-60) [ 24 ]. Consequently, many pharmaceutical agents acting at the σRs have been used in the treatment of cancer and are receiving considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these considerations and as part of our ongoing research, we herein focus on the development of an efficient protocol based on the three-component one-pot Mannich reaction for the preparation of a β-amino ketone small library endowed with general formula A ( Figure 2 ), consisting of a tertiary amine bridged to an aromatic ring by a propylenic chain. The final aim is to discover new potential sigma receptor (SR) modulators [ 29 , 30 , 31 , 32 ]. We set up an efficient, clean, quick, and scalable protocol based on microwave-assisted organic synthesis (MAOS), using cerium ammonium nitrate (CAN) as a catalyst and polyethylene glycol 400 (PEG 400) as a solvent, combined with polymer-assisted solid phase synthesis (PASPS).…”
Section: Introductionmentioning
confidence: 99%